Digital Marketing Training: MSME Efforts Towards International Markets - Joko Setiyo; Imam Mukhlis; Fulgentius Danardana Murwani (Mahameru Publisher, 2022)
Batik MSMEs currently need to apply the concept of digital marketing in order to compete in the global market and increase sales. There are still some Batik MSME actors who use conventional marketing. This study aims to apply a digital marketing training and mentoring model to Batik Cahaya SMEs in Lumajang Regency, East Java, Indonesia. This study uses an ethnographic approach by collecting from literature sources and field data from observations, participation, and interviews. The results showed that the digital marketing training and mentoring model was very effective and had a positive impact. Some of the benefits obtained are ease of marketing products, time efficiency, minimizing costs, ease of transactions, and unlimited reach to international markets. There was an increase in sales of up to 13% during the six months after the activity took place.